2015
DOI: 10.1007/s00128-015-1615-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cytotoxicity of Vanadium to CHO-K1 Cells in the Presence of Inorganic Selenium

Abstract: The effect of selenium applied as sodium selenite (Na2SeO3) on the cytotoxicity of vanadyl sulphate (VOSO4) was examined using CHO-K1 cells. From the resazurin-based assay, it appears that Na2SeO3 at low doses (0.5 and 1 μM) can enhance 100 μM VOSO4-induced cell damage. The two-way ANOVA analysis revealed that the increased cell damage was a consequence of a synergistic interaction of 0.5 μM Na2SeO3 with VOSO4 and 1 μM Na2SeO3 with VOSO4. Observations performed with a phase-contrast microscope showed most cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In addition, laboratory-based studies conducted in animal models or cell cultures found that vanadium exposure can induce a variety of toxic effects such as cardiovascular effects (e.g., vascular endothelial dysfunction [30] and arterial hypertension [31]), immune toxicity (e.g., damage to the spleen [32] and thymus [33]), neurotoxicity (e.g., hippocampal alterations [34] and memory loss [35]), developmental disturbances (e.g., increased embryolethality and skeletal defects [36]), and pulmonary toxicity [37]. It should be added that, besides the dose of vanadium and the route of vanadium exposure, many other factors such as the form of vanadium (inorganic versus organic forms) and interactions with other elements such as selenium [38,39] or magnesium [40] can also influence vanadium toxicity (depicted in Figure 1).…”
Section: Overview Of Vanadiummentioning
confidence: 99%
“…In addition, laboratory-based studies conducted in animal models or cell cultures found that vanadium exposure can induce a variety of toxic effects such as cardiovascular effects (e.g., vascular endothelial dysfunction [30] and arterial hypertension [31]), immune toxicity (e.g., damage to the spleen [32] and thymus [33]), neurotoxicity (e.g., hippocampal alterations [34] and memory loss [35]), developmental disturbances (e.g., increased embryolethality and skeletal defects [36]), and pulmonary toxicity [37]. It should be added that, besides the dose of vanadium and the route of vanadium exposure, many other factors such as the form of vanadium (inorganic versus organic forms) and interactions with other elements such as selenium [38,39] or magnesium [40] can also influence vanadium toxicity (depicted in Figure 1).…”
Section: Overview Of Vanadiummentioning
confidence: 99%
“…Sodium orthovanadate also inhibits oral squamous, colon and kidney cancer cell proliferation and triggers apoptosis with similar concentrations as the one we report (Khalil & Jameson, ; Klein et al, ) in a manner similar to sodium metavanadate; nevertheless, these reports only mention as possible cause the crosstalk between different signaling phosphoproteins, possibly p53 through the ATM pathway (Suzuki et al, ). Their effect on disruption of cell signaling transduction pathways, cell cycle arrest and apoptosis seem to be valence dependent (Paulpandiyan & Raman, ; Tian et al, ; Wu et al, ; Wu et al, ; Zwolak, ) but the precise cytotoxic mechanism of vanadium compounds remains undetermined (Taddei, Giannoni, Fiaschi, & Chiarugi, ). Therefore, we investigated the mechanisms responsible for NaVO 3 and VOSO 4 cytotoxic activity as each one is representative of biologically important valences of vanadium (Al‐Majed, ; Duprez, Wirawan, Vanden Berghe, & Vandenabeele, ; Kordowiak, Klein, Goc, & Dabros, ; Zwolak, ).…”
Section: Discussionmentioning
confidence: 99%
“…Their effect on disruption of cell signaling transduction pathways, cell cycle arrest and apoptosis seem to be valence dependent (Paulpandiyan & Raman, 2017;Tian et al, 2016;Wu et al, 2014;Wu et al, 2016;Zwolak, 2015) but the precise cytotoxic mechanism of vanadium compounds remains undetermined (Taddei, Giannoni, Fiaschi, & Chiarugi, 2012). Therefore, we investigated the mechanisms responsible for NaVO 3 and VOSO 4 cytotoxic activity as each one is representative of biologically important valences of vanadium (Al-Majed, Duprez, Wirawan, Vanden Berghe, & Vandenabeele, 2009;Kordowiak, Klein, Goc, & Dabros, 2007;Zwolak, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has to be used carefully as, at high concentrations, selenium can display pro-oxidant properties and generate ROS (Lee & Jeong, 2012). Concentrations of selenium below 1 µM have been shown to be safe for CHO-K1 cells and are often included in cell culture medium (Zhang, Robinson, & Salmon, 2006;Zwolak, 2015). However, toxic concentrations of selenium have to be determined for each cell line.…”
Section: Trace Elements and Chelatorsmentioning
confidence: 99%